Seasonal and environmental drivers of antibiotic resistance and virulence in Escherichia coli from aquaculture and their public health implications - Aya El Badawy; Dalia Hamza; Zeinab Ahmed; Maha A. Sabry (Scientific Reports)
Abstract Aquaculture is increasingly impacted by environmental stressors such as temperature and pH fluctuations, which influence the proliferation and antibiotic resistance of Escherichia coli (E. coli). This study investigates the effects of these factors on the prevalence, virulence, and antibiotic resistance of E. coli isolated from aquaculture environments in Egypt, with a focus on public health implications. A total of 328 Oreochromis niloticus (Nile tilapia) samples were collected from Egyptian fish farms over five sampling periods, representing different seasonal conditions. E. coli was isolated and identified using selective culture methods and biochemical tests. Molecular characterization was conducted via polymerase chain reaction (PCR) to detect diarrheagenic E. coli pathotypes (st, lt, eaeA, bfpA, stx1, stx2). Additionally, PCR was utilized to screen for β-lactamase and carbapenemase resistance genes. Water parameters, including temperature and pH, were recorded, and their correlation with bacterial prevalence, virulence, and antibiotic resistance profiles were analyzed. A high prevalence of E. coli (92.68%) was observed, with a significant correlation between bacterial occurrence and elevated water temperatures. Diarrheagenic E. coli was detected in 82.1% of samples, with enterotoxigenic E. coli (ETEC) being the most common pathotype. Some isolates harbored multiple virulence genes, indicating hybrid strains. Resistance genes such as bla TEM, bla CTX-M, and bla OXA-48 were widely distributed, particularly during warmer months and at neutral pH levels. Groups with elevated water temperatures exhibited a higher prevalence of antibiotic-resistant isolates, often harboring multiple resistance genes. This study highlights the significant role of environmental stressors in influencing the prevalence, pathogenicity, and antibiotic resistance profiles of E. coli in aquaculture systems. The findings emphasize the need for continuous monitoring and improved biosecurity measures to mitigate the risks associated with MDR E. coli in aquaculture, ensuring food safety and protecting public health.